KAZAKHSTAN AND ESTONIA: EVALUATION OF PREFERENCES IN INTERMARRIAGES - Vladimir Kozlov (Население и экономика, 2017)
This paper is devoted to the "ethnic" preferences in partners’ choice for the inter-ethnic marriages inEstoniaandKazakhstan(countries with the share of Russians more than 20% in the total population). As a measure for the preferences the author uses inter-ethnic distance and for the calculation national census data by nationality and marriage status are used.